Selected Areas in Cryptography 19th International Conference, SAC 2012, Windsor, Canada, August 15-16, 2012, Revised Selected Papers - Knudsen, Lars R.; Wu, Huapeng (Security and Cryptology ;, 2013)
This book constitutes the thoroughly refereed post-conference proceedings of the 19th International Conference on Selected Areas in Cryptography, SAC 2012, held in Windsor, Ontario, Canada, in August 2012. The 24 papers presented were carefully reviewed and selected from 87 submissions. They are organized in topical sections named: cryptanalysis, digital signatures, stream ciphers, implementations, block cipher cryptanalysis, lattices, hashfunctions, blockcipher constructions, and miscellaneous.